2022
DOI: 10.3390/environments9030031
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach for Evaluating the Restoration of the Salinity Gradient in Transitional Waters: Monitoring and Numerical Modeling in the Life Lagoon Refresh Case Study

Abstract: Large lagoons usually show a salinity gradient due to fresh water tributaries with inner areas characterized by lower mean values and higher fluctuation of salinity than seawater-dominated areas. In the Venice Lagoon, this ecotonal environment, characterized in the past by oligo-mesohaline waters and large intertidal areas vegetated by reedbeds, was greatly reduced by historical human environmental modifications, including the diversion of main rivers outside the Venice Lagoon. The reduction of the fresh water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This project was scientifically assessed in two publications. The impact of the measure on variations of salinity in space and their fluctuations in time was studied using a before/after comparison and monitoring combined with hydrodynamic modelling [27]. The observed fluctuations corresponded quite well with the simulation results and corresponded to desired results in the field.…”
Section: Interventions In Hydrodynamics For Ecological Restorationsupporting
confidence: 59%
See 1 more Smart Citation
“…This project was scientifically assessed in two publications. The impact of the measure on variations of salinity in space and their fluctuations in time was studied using a before/after comparison and monitoring combined with hydrodynamic modelling [27]. The observed fluctuations corresponded quite well with the simulation results and corresponded to desired results in the field.…”
Section: Interventions In Hydrodynamics For Ecological Restorationsupporting
confidence: 59%
“…A more ambitious program, a real ecological restoration project, has been pursued by the LIFE LAGOON REFRESH project, which aims at restoring the freshwater-saltwater gradients through the diversion of freshwater flow from the Sile river into the Venice lagoon [26][27][28]. This was aimed at restoring the conditions existing before the 17th century, when the Sile river was a tributary in the northern part of the lagoon [10].…”
Section: Interventions In Hydrodynamics For Ecological Restorationmentioning
confidence: 99%
“…As planned, the restoration of salinity gradient was reached in the intervention area of 70 ha. Indeed, starting from >30 (annual mean salinity before project) at the whole area, the salinity has resulted less than 5, in 5 ha; less than 15, in 25 ha; and less than 25, in 70 ha after the interventions (Feola et al, 2022).…”
Section: Restoration Of Salinity Gradientmentioning
confidence: 99%
“…The period to assess these results was set within 5 years after the end of the project and monitoring activities are still ongoing. Currently the result concerning salinity gradient was achieved (Feola et al, 2022), and the first outcomes of fish fauna assessments indicated a quite positive response (see Species increasing). Based on expectations, the other indicators for habitat structures and functions will take a longer time to respond to the environmental changes.…”
Section: Habitat Restorationmentioning
confidence: 99%
“…The role of valli da pesca as buffers and as conservation opportunities leads also to consider how important it might be to restore a buffer strip between the land and the lagoon, which has been lost in some areas. As the valli da pesca prove to be effective in maintaining saltmarshes, reed meadows and ecological gradients, similarly it might be useful to consider ecological restoration efforts in areas that are most affected by the transfiguration of the original lagoon landscape (Feola et al, 2022).…”
Section: )mentioning
confidence: 99%